Land Cover and Land Surface Temperature in the West Bank, Palestine - Ayah Helal; Zahraa Zawawi (Advances in Civil Engineering)
The 10 major cities in the West Bank (WB), Palestine—Nablus, Ramallah and Al-Bireh, Jenin, Qalqilia, Salfit, Tubas, Jericho, Bethlehem, Tulkarem, and Hebron—are experiencing rapid urban transformation and changing land cover. This study explores the relationship between land cover (built-up and unbuilt areas) and soil type in these cities across benchmark years 1995, 2000, 2005, 2010, 2015, and 2021. In addition to the former, the paper argues that the expansion and increase of the built-up area and the change in soil type of the aforementioned cities in the West Bank, Palestine, are leading to changes in the land surface temperature (LST). This conclusion was reached through a methodological framework that was developed to measure the relationship between the changing land cover (built-up and unbuilt-up areas), soil type, and LST in the 10 major cities in the region. The framework relies on data retrieved through remote sensing in the years from 1995 to 2021. The results of the analysis conducted through this methodological framework showed that there is an inverse relationship between the increase in built-up areas and LST; however, LST is less inside the built-up areas than in the surrounding areas (open spaces) due to different land cover (unbuilt area with grass and shrubs) and different soil type.